2022
DOI: 10.3390/s22062219
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced Seismic Event Discrimination Using Supervised Machine Learning

Abstract: The discrimination between earthquakes and artificial explosions is a significant issue in seismic analysis to efficiently prevent and respond to seismic events. However, the discrimination of seismic events is challenging due to the low incidence rate. Moreover, the similarity between earthquakes and artificial explosions with a local magnitude derives a nonlinear data distribution. To improve the discrimination accuracy, this paper proposes machine-learning-based seismic discrimination methods—support vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, the model obtained accuracy of 98% and 97.5% based on distinctive features, as reported by (Abdalzaher et al, 2021, andL. Dong et al, 2014) accuracy of 73% and 86% as reported by Ahn, H. et al, 2022 andAbdalzaher et al, 2021 in that order.…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…On the other hand, the model obtained accuracy of 98% and 97.5% based on distinctive features, as reported by (Abdalzaher et al, 2021, andL. Dong et al, 2014) accuracy of 73% and 86% as reported by Ahn, H. et al, 2022 andAbdalzaher et al, 2021 in that order.…”
Section: Resultsmentioning
confidence: 62%
“…In the time domain waveform, the SVM model produced results with 66% accuracy, which translates to 99.4% accuracy based on feature extraction. According to study findings by Ahn, H. et al (2022), Kim et al (2020), Abdalzaher et al (2021), and L. Dong et al (2014), this model's accuracy was 93.7%, 95.5%, 86% and 96.3% respectively, based on distinguishing traits.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations